Predictive factors of achieving therapeutic goals of hypertriglyceridemia. (January 2014) - Pintó, X.; Valdivielso, P.; Perez de Juan, J.M.; Plana, N.; Garcia-Arias, C.; Fuentes, F.J.; Hernández-Mijares, A.; Mostaza, J.M.; ,
Abstract Objectives: The aim of this study was to ascertain the factors associated with non-achievement of triglyceride (TG) goals in a cohort of hypertriglyceridemic patients attending the lipid clinics of the Spanish Arteriosclerosis Society (LC-SAS). Methods: Patients with high TG levels (>2.2 mmol/L; 200 mg/dL) were included in this multicenter, prospective, observational study and followed up for 1 year. The TG goal was ≤2.2 mmol/L (200 mg/dL). Main limitations of this study are that etiologic diagnosis of hypertriglyceridemia was not done under unified criteria and drug compliance was not evaluated. Results: From 1394 patients initially included in the study, 929 (age range: 50 ± 12 years, 26% women) were followed up for 1 year; 523 patients (56%) failed to reach the TG target. These patients were younger, had a higher body mass index (BMI), were more frequently smokers, hypertensive and diabetic and had more severe dyslipidemia. They were also more sedentary, their diet was of poorer quality and they had higher alcohol consumption. The independent predictors of treatment failure were hypertriglyceridemia severity, low high density lipoprotein cholesterol (HDL-C), and high non-HDL-C, alcohol consumption and a raised BMI, while drug treatment had no predictive power. Conclusion: Independent predictors of failure to achieve hypertriglyceridemia treatment goals are inappropriate lifestyle, evidenced by insufficient weight loss, alcohol consumption and dyslipidemia severity.